Study of Structural and Electronic Properties of Fluoride Perovskite KCaF3 using FP-LAPW Method - Neupane, K.; Thapa, R. K. (Himalayan Physics, 2017)
To study the structural and electronic properties of cubical perovskite KCaF3, the first principles calculation within the full potential linearized augmented plane wave (FP-LAPW) method is applied. The exchange correlation effects are included through the GGA exchange potential. The calculated structural properties such as equilibrium lattice constant, the bulk modulus and its pressure derivative are in agreement with the published results of other authors. From our study we have found that the band gap of KCaF3 is 6.4 eV which is the indication of insulating behavior. The Himalayan Physics Vol. 6 & 7, April 2017 (100-103)